Review Artikel: Tanaman Gaharu (Aquilaria malaccensis L.) sebagai Antioksidan - Ghiffari, Muhammad; Fevria, Resti (Lembaga Yasin AlSys, 2024)
Indonesia is renowned for the variety of its plant life. Although poorly managed, Indonesia is a mega-biodiversity nation with a wealth of medicinal plants and significant development potential. Owned natural resources have benefited people's everyday lives in addition to being used as food and traditional medicine. Gaharu is a type of biodiversity that has the potential to be used in traditional medicine. Aquilaria agaloccha Rox, a member of the Thymeliaceae family, is the source of gaharu, however it can also be found in plants from the Leguminoceae and Euphorbiaceae families. The general populace believes that gaharu leaves can decrease blood pressure and act as an antioxidant. The Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) technique is the research methodology utilized in literature review articles. Publish or Perish, (2010-2023), is the text that was utilized. Gaharu (Aquilaria malaccensis L.) is a plant that may create secondary metabolites in the form of phenols, terpenoids, flavonoids, glycosides, tannins, and steroids/triterpenoids, all of which are potent antioxidants, according to the findings of a literature study.